2016
DOI: 10.1093/jxb/erw122
|View full text |Cite
|
Sign up to set email alerts
|

Expression ofVitis amurensis NAC26in Arabidopsis enhances drought tolerance by modulating jasmonic acid synthesis

Abstract: Highlight VaNAC26, a member of the NAC gene family from the wild species Vitis amurensis, plays an important role in drought tolerance by positively modulating jasmonic acid synthesis and enhancing the antioxidant system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 65 publications
2
45
0
Order By: Relevance
“…JA has significant roles in mediating stress responses and regulating growth and development of plants (Ullah et al ). JA has been reported to induce plant drought tolerance through multiple strategies, such as scavenging of ROS, stomatal closure and root development (Sánchez‐Romera et al , Kazan , Fang et al , Ullah et al ). The increase in α‐linolenic acid might provide the potential for JA increase to cope with drought.…”
Section: Discussionmentioning
confidence: 99%
“…JA has significant roles in mediating stress responses and regulating growth and development of plants (Ullah et al ). JA has been reported to induce plant drought tolerance through multiple strategies, such as scavenging of ROS, stomatal closure and root development (Sánchez‐Romera et al , Kazan , Fang et al , Ullah et al ). The increase in α‐linolenic acid might provide the potential for JA increase to cope with drought.…”
Section: Discussionmentioning
confidence: 99%
“…JA, which is naturally synthesized by plants, plays an important role as a signal molecule that induces tolerance mechanisms under the influence of abiotic stresses456789101151. However, the roles of the JA signalling pathway in response to abiotic stresses in sweet potato have not been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that jasmonic acid (JA, or the related compound methyl jasmonate, MeJA) functions in diverse physiological processes in plants, such as the regulation of plant responses to abiotic stresses4567891011. The exogenous application of JA to wheat seedlings for three days has been shown to significantly enhance the salt tolerance of these plants by increasing the activities of antioxidant enzymes and the concentrations of antioxidative compounds4.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The roots were harvested, rinsed briefly in phosphate‐buffered solution, immediately frozen in liquid nitrogen and ground into a powder, after which they were extracted with methanol–water (8 : 2) at 4 °C. Endogenous jasmonates (JA, MeJA and JA‐Ile) were quantified using HPLC‐MS/MS as described previously (Fang et al ., ). Three biological replicates per line were analysed.…”
Section: Methodsmentioning
confidence: 97%